UMP postgraduate student created her own skin care product - RenoSkin - Siti Nurfarmy, Ibrahim (2019)
One of the keys to success is high commitment, something postgraduate student Nor Mahirah Mustapha has showed for she is now a proud owner of her own skin care product called RenoSkin that has sold more than 25,000 units since 2016.